Faktor - Faktor yang Mempengaruhi Pendapatan Petani Padi Sawah di Desa Gambah Kecamatan Barabai Kabupaten Hulu Sungai Tengah - Muhammad Rizki; Rusdiansyah Rusdiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was conducted to find out: (1) the influence of seed costs, fertilizer costs, land rental costs, and labor costs on the income of rice farmers in Gambah Village, Barabai District, Hulu Sungai Tengah Regency. (2) The most dominant factor in influencing the income of rice farmers.            This study used quantitative research using primary data from 69 farmers. The data obtained is processed using multiple regression analysis with SPSS software version 21.            The result of the research is that simultaneously, free variables together have a significant effect on bound variables. While in part, the variable cost of fertilizer does not affect the income of rice farmers. The most dominant factor in influencing the income of rice farmers is the cost of land rent.